Implementation of an omnidirectional antenna on a 4G repeater with a working frequency of 1800 MHZ - Ade Silvia Handayani; Nasron Nasron; Rivaldo Arviando; Abu Hasan; Sopian Soim (Faculty of Engineering, Universitas Sultan Ageng Tirtayasa, 2021)
In this study, an omnidirectional antenna is used as a 4G signal amplifier with a frequency of 1800 Mhz. Omnidirectional antennas typically have a gain of about 3-12 dBi. The application of an omnidirectional antenna on a 4G signal amplifier repeater is used as a donor antenna facing the base transceiver station (BTS) source. Applying an omnidirectional antenna as a donor antenna will allow signal transmission from all directions to the BTS to be received from all directions. This antenna will serve or only emit signals in the vicinity of 360 degrees. While at the top of the antenna, there is no radiation signal. The voltage standing wave ratio (VSWR) test results with the MMANA test software get a reading of <1.5, with an impedance of 49 ohms and a gain of >6.5 dB. The radiation distribution pattern from the plotting results shows a circular spread of 360 degrees. This antenna is suitable for donor antennas that can receive signals from the BTS from all directions from the angle of incidence. From testing with an open signal application and comparing parameters before and after using a repeater, the download speed increased from 0.2 Mbps to 2.3 Mbps, and the latency increased from 159 ms to 73 ms. The scanning spectrum in auto mode gets a mid-frequency reading of 1867.20Mhz when the repeater is on. The results achieved in the service of this 4G signal booster tool are being able to understand 5th generation materials such as 5G technology. Several countries have started to study 5G technology by forming consortiums such as METIS, 5GNOW, and others. Pada penelitian ini digunakan antena omnidirectional sebagai penguat sinyal 4G dengan frekuensi 1800Mhz. Antena omnidirectional biasanya memiliki penguatan sekitar 3-12 dBi. Penerapan antena omnidirectional pada repeater penguat sinyal 4G digunakan sebagai antena donor yang menghadap ke sumber base tranceiver station (BTS). Penerapan antena omnidirectional sebagai antena donor akan memungkinkan transmisi sinyal dari segala arah ke BTS dapat diterima dari segala arah. Antena ini akan melayani atau hanya memancarkan sinyal di sekitarnya atau 360 derajat. Sedangkan di bagian atas antena, tidak ada sinyal radiasi. Hasil pengujian voltage standing wave ratio (VSWR) dengan software uji MMANA mendapatkan pembacaan <1,5, dengan impedansi 49 ohm dan gain >6,5 dB. Pola sebaran radiasi dari hasil plotting menunjukkan penyebaran melingkar sebesar 360 derajat. Antena ini cocok untuk antena donor yang dapat menerima sinyal dari BTS dari segala arah dari sudut datang. Dari pengujian menggunakan aplikasi open signal, didapatkan perbandingan parameter sebelum dan sesudah menggunakan repeater, dari kecepatan download 0.2 Mbps menjadi 2.3 Mbps dan peningkatan latency dari 159 ms menjadi 73 ms. Spektrum pemindaian dalam mode otomatis mendapatkan pembacaan frekuensi tengah 1867.20Mhz saat repeater aktif. Hasil yang dicapai di pengabdian alat penguat sinyal 4G ini adalah dapat memahami materi generasi ke-5 seperti teknologi 5G. Seperti beberapa negara telah memulai mengkaji teknologi 5G dengan membentuk konsorsium seperti METIS, 5GNOW, dan lainnya.